Defining the human sperm microtubulome: an integrated genomics approach†. Issue 1 (20th December 2016) - Jumeau, Fanny; Chalmel, Frédéric; Fernandez-Gomez, Francisco-Jose; Carpentier, Céline; Obriot, Hélène; Tardivel, Meryem; Caillet-Boudin, Marie-Laure; Rigot, Jean-Marc; Rives, Nathalie; Buée, Luc; Sergeant, Nicolas; Mitchell, Valérie
Abstract: Sperm motility notably depends on the structural integrity of the flagellum and the regulation of microtubule dynamics. Although researchers have started to use "omics" techniques to characterize the human sperm's molecular landscape, the constituents responsible for the assembly, organization, and dynamics of the flagellum microtubule have yet to be fully defined. In this study, we defined a core set of 116 gene products associated with the human sperm microtubulome (including products potentially involved in abnormal ciliary phenotypes and male infertility disorders). To this end, we designed and applied an integrated genomics workflow and combined relevant proteomics, transcriptomics, and interactomics datasets to reconstruct a dynamic interactome map. By further integrating phenotypic information, we defined a disease-interaction network; this enabled us to highlight a number of novel factors potentially associated with altered sperm motility and male fertility. Lastly, we experimentally validated the expression pattern of two candidate genes ( CUL3 and DCDC2C ) that had never previously been associated with male germline differentiation. Our analysis suggested that CUL3 and DCDC2C 's products have important roles in the sperm flagellum. Taken as a whole, our results demonstrate that an integrated genomics strategy can highlight relevant molecular factors in specific sperm components. This approach could be easily extended by including other "omics" data (from asthenozoospermic men, for example) and identifying other critical proteins from the human sperm microtubulome. Summary Sentence: Although researchers have started to use "omics" techniques to characterize the human sperm's molecular landscape, the constituents responsible for the assembly, organization, and dynamics of the flagellum microtubule have yet to be fully defined.